Mutu Bakteriologis Saus Tomat Pentol di Banjarbaru - Ratih Dewi Dwiyanti; Leka Lutpiatina (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2016)
Abstract: The food was used as a complementary flavor sauces include snacks bulb. Dressing materials according to SNI 01-7388-2009 must comply with the requirements of the parameter Staphylococcus aureus, MPN (Most probable number) Coliform, TPC (total plate count) and molds. This study aims to determine the percentage of tomato sauce snacks bulb in the area around the intersection of four Banjarbaru who do not qualify SNI 01-7388-2009 of parameters MPN Coliform and Staphylococcus aureus. The results showed MPN Coliform tomato sauce ranges from 0-240 and Staphylococcus aureus 5 x 101 to 6.5 x 103. Concluded percentage tomato sauce snacks bulb that does not qualify SNI 01-7388-2009 parameter is 60% MPN Coliform and Staphylococcus aureus 80%. Suggestions to determine the value of TPC (total plate count) and molds and other chemical parameters of tomato sauce.